Pembelajaran Guru PAI Terhadap Anak Inklusi di SDN 04 Birugo Bukittinggi - Riani, Mei Elva; Dewi , Putri Andam; Romodon, Romodon (Indonesian Research Journal on Education, 2023)
Education is a need for humans, not only normal people but those with disabilities/children with special needs. Vulnerable children are excluded and neglected from education, it can also be said as children who have special needs in education (children with special education needs). Inclusive education is a system of educational services for children with special needs in normal classes together with their peers. So that inclusive education is an education delivery system that provides an opportunity for students whohave disabilities and have the potential for intelligence or special talents to participate in education or learning in an educational environment simultaneously with students in general. School is a formal educational institution, where the founder aims to educate, manage and provide teaching by educators to their students. Schools are also places to receive education, where education is a right for everyone, including children with special needs or ABK. The goal to be achieved in this study is to describe the learning of PAI teachers towards the incubation of children at SDN 04 Birugo Bukittinggi. The researchmethod used is descriptive method with data collection techniques through observation and interviews. And the object of this research is one of the teachers in the PAI field of study.